Sylvanas - Golden, Christie (World of warcraft (New York, N.Y.), 2022)
"Sylvanas Windrunner has borne many titles. To some, she is a hero--to others, a villain. But whether in pursuit of justice, vengeance, or something more, Sylvanas has always sought to control her own destiny The power to achieve her goals has never been closer, as Sylvanas works alongside the Jailer to liberate all Azeroth from the prison of fate. Her final task? Secure the fealty of their prisoner--King Anduin Wrynn"--